On Some Critical Concepts of Magnetic Pulse Welding Technology - Manjusree, Palivela; Rao, Pasumarthi Mallikarjuna (Journal of Advanced Research in Instrumentation and Control Engineering; Vol 8 No 3&4 (2021): Journal of Advanced Research in Instrumentation and Control Engineering, 2022)
Electromagnetic pulse welding technology is a relatively new manufacturing, promising and attractive technology emerging these days. Electromagnetic pulse welding is achieved by impact where the pieces to be welded are accelerated towards each other by the Lorentz force established between the two. This welding technology works to weld for both similar and dissimilar metals within a few microsecs which is found to be difficult to get welded by conventional welding methods. An attempt is made to study the phenomena of electromagnetic pulse welding of both similar and dissimilar metals. SS316L tube having diameter of 6.5 mm, with a thickness of 0.5 mm is welded to SS316L rod such that it discharges a very peak current of 130 KA at 25.65 μs. Another similar metal combination of Aluminium 6061 tube having diameter of 6.5 mm, with a thickness of 0.5 mm is welded to Aluminium 6061 Flange. Standoff distance of 1 mm is chosen to move the job piece so that it grasps to gain maximum velocity to have the impact on the Aluminium 6061 tube to Aluminium 6061 flange produced a very high discharge current of around 161 KA at 32 μs Electrical circuit consists of capacitance of 2 μF, circuit’s total inductance of 2 nH and resistance of 0.02Ω is considered. Dissimilar metal combination of Cu-DHP tube of diameter 22.22 mm is welded to 11S MnPb 30 steel target tube. Discharge electrical circuit consists of a resistance of 14.3 mΩ with circuit inductance of 0.55 μH and a capacitor bank of 160 μF discharges a peak current of 160.1 KA at 21.38 us has been observed from Matlab programming. How to cite this article: Manjusree P, Rao PM. On Some Critical Concepts of Magnetic Pulse Welding Technology. J Adv Res Instru Control Engg 2021; 8(3&4): 1-5. DOI: https://doi.org/10.24321/2456.1398.202102